Comparison of 8-weeks of full versus split body resistance training on appetite and energy intake in non-obese untrained men - Cardoso, Larissa Kelly; Panissa, Valéria L. G. [UNESP]; Cholewa, Jason Micheal; Santana, Nathanael Leal; Brito, Aldeni Silva; Barros, Clara Andressa; Barros, Esmeralda Maria Lustosa; de Moura, Rayane Carvalho; Monteiro, Paula A.; Rossi, Priscila A. Q. [UNESP]; Vieira, Matheus Mesquita [UNESP]; Brito, Ahecio Kleber Araujo; et al. (Springer Nature, 2024)
To investigate the effects of 8-weeks of full versus split body resistance training (RT) on appetite and energy intake in non-obese untrained men. The participants were pair-matched based on their initial fat mass and then randomly allocated into one of two treatment groups: Full body (FB, n = 20), in which all muscle groups were trained in every session, or Split body (SB, n = 15), in which upper and lower muscle groups were trained alternated per session; both groups trained in non-consecutive days, three times per week with total number of sets performed equated between groups. Energy intake, body composition, and strength performance were evaluated at pre-training, and after 8-weeks of RT, as well as self-reported hunger, fullness, and desire to eat, that were assessed at fasted and feed states pre- and post-intervention. FB and SB resistance training increased fat-free mass (FFM) (p < 0.001); and FB induced greater maximal strength improvement (p = 0.027). At fasted state self-reported hunger increased, and fullness decreased, while in feed state desire to eat something fatty increased in both groups. Carbohydrate intake (p = 0.011) decreased in both groups. In conclusion, FB and SB training increased orexigenic drive (increasing hunger and decreasing fullness), however, total energy intake and fat mass did not change after 8-weeks of RT in non-obese untrained men. Registered under Brazilian Registry of Clinical Trials no. RBR-3wkcvyw.